Microcooling system with impinging jets and a stalactite structure. (17th June 2016) - Kim, Sun-Min; Kim, Kwang-Yong
ABSTRACT: A novel structure for a microcooling system with an impinging jet array was proposed to enhance heat transfer and reduce the pressure drop. Conjugated heat transfer in the proposed impinging jet array cooling systems, with and without effusion holes, was analyzed to evaluate their heat transfer performance and pressure drop using the three-dimensional Navier–Stokes equations for steady incompressible laminar flow. Grid dependency tests were performed for not only the size, but also the distribution of the grid system. The numerical result was validated using the experimental data. The area-averaged Nusselt number and the maximum temperature on the target surface were selected as the performance parameters for heat transfer. The proposed structure showed remarkable improvement in both the heat transfer performance and pressure drop, but natural effusion from the system did not improve the performance.